A novel 12-marker panel of cancer-associated fibroblasts involved in progression of hepatocellular carcinoma - Zou B; Liu X; Gong Y; Cai C; Li P; Xing S; Pokhrel B; Zhang B; Li J (Cancer Management and Research, 2018)
Baojia Zou,1,* Xialei Liu,1,* Yihang Gong,1,* Chaonong Cai,1 Peiping Li,1 Shan Xing,2 Bibesh Pokhrel,1 Baimeng Zhang,1 Jian Li1 1Department of Hepatobiliary Surgery, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai 519000, China; 2Department of Clinical Laboratory, Sun Yat-sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangzhou 510060, China *These authors contributed equally to this work Background/Aim: Cancer-associated fibroblasts (CAFs) are important factors in the progression of hepatocellular carcinoma (HCC). But the characterization of these cells remains incomplete. This study aims to identify a panel of markers for CAFs that are associated with HCC progression. Materials and methods: The sequencing data and clinicopathological characteristics of 366 patients were obtained from the Cancer Genome Atlas (TCGA) database (366 HCC tissues and there were 50/366 cases with corresponding normal liver tissues). In vitro validation of the markers was performed by quantitative real-time PCR using the hepatic stellate cell line LX2 induced by the HCC cell line Huh7. The activation of LX2 was confirmed by α-smooth muscle actin and fibroblast activation protein, using quantitative real-time PCR and immunofluorescence staining. In vivo detections of the 12 markers were done in 40 tissue samples (30 HCC and 10 normal). Results: We successfully identified 12 CAF markers from TCGA data: FGF5, CXCL5, IGFL2, MMP1, ADAM32, ADAM18, IGFL1, FGF8, FGF17, FGF19, FGF4, and FGF23. The 12-marker panel was associated with the pathological and clinical progressions of HCC. All 12 markers were upregulated in vitro. In vivo expressions of these markers were paralleled with those in TCGA data. Conclusion: A 12-marker panel of CAFs in HCC is identified, which is associated with both pathological and clinical progressions of cancer. Keywords: hepatocellular carcinoma, cancer-associated fibroblasts, CAFs marker panel, TCGA database analysis, transcriptome profiling